Escala de distúrbios do sono em crianças: tradução, adaptação cultural e validação - Ferreira, Vanessa Ruotolo [UNIFESP] (2009)
Introduction: The Sleep Disturbance Scale for Children (SDSC) is a 26-item instrument for evaluating sleep among children aged 3-18 years. It differentiates among conditions such as disorders of initiating and maintaining sleep, sleep breathing disorders, disorders of arousal, sleep-wake transition disorders, excessive somnolence, and sleep hyperhydrosis. The aim os this study was to translate, culturally adapt, and validate it for Brazilian Portuguese. Method: The study was carried out in two phases: (1) forward translation, back translation, pretesting, and calculation of sample size; (2) validation: reliability (Cronbach´s alpha), convergent analysis (Pearson correlation), and discriminatory validity (comparing scores of the test with the results of polysomnography). One hundred children, aged 3-18 years, accompanied by their parents and/or guardians participated in the phases. PSG studies have been done to calculate the sample size and validation. Results: The scale instructions and items were adapted regarding semantic, experiential, conceptual, and cultural equivalence validation. The scale structure related to visual communication was also adapted to Brazilian population preference and habits, and this resulted in a chart with clear instructions and easy recognition of the statements and possible responses. Reliability analysis showed values greater than 0.55. There has been reasonable convergent validity only for SDB. Discriminatory validity using the PSG study for positive sleep-disordered breathing (SDB) was 8.9, attesting discriminatory validity only for SDB.The three questions of the scale can screen SDB. Conclusion: The SDSC was translated and validated for Brazilian Portuguese, and it presented internal consistency, convergent and discriminatory validity. It can be used in population-based studies in order to screen sleep-disordered breathing in children.